ANATOMICAL VARIATIONS IN ARTERIAL SUPPLY OF THUMB AND INDEX FINGER IN CADAVERIC HANDS - INAM, T; TAFWEEZ, R; BUKHARI, ZH; KHALID, W (Biological and Clinical Sciences Research Journal, 2022)
Human hand is highly evolved in terms of complexity and variations. In this modern medical era, vascular anatomy of the human hand has clinical importance in medical, surgical and radiological sciences. The intention of the current study is to determine the variations which occur as the radial artery branches thus making a contribution to the arterial supply of the index finger and the thumb. The study design was descriptive case series, carried out in the Department of Anatomy in King Edward Medical University from December 2018 to May 2019 on 30 cadaveric limbs. Vivisection of the cadaveric hands was performed following Cunningham’s Manual of practical anatomy. The origin and the course of RA, UA and MA were dissected and identified with further exploration of the blood supply of the index finger and the thumb. All details were entered in a predesigned proforma, and the dissected limbs were photographed. Data was analyzed to find the frequencies of superficial palmar arch as well as the arterial supply of thumb and index finger were also expressed in frequencies. Great variation was observed in the arterial supply to palmar aspect of index finger and thumb. Main contributing artery being radial artery in majority of cases through its common palmar or proper palmar branches arising from SPA or SPBRA. Ulnar artery and median artery were also observed to be supplying these areas in 6.6% and 3.3% cases respectively. The median artery when present was replacing the radial artery on palmar aspect of hand. The dorsum, however, was supplied by the princeps pollicis and the radialis indicis branches of radial artery in all the cases. We concluded that in about 1/3rd (11/30 are incomplete SPA) of our studied sample, arterial supply of the index finger and the thumb is highly dependent on radial artery and should any damage occur to it, vitality of these useful structures will be compromised.